Labor-related knowledge transfers from Chinese foreign direct investment in Ethiopia and Tanzania - Ellis, Mia; McMillan, Margaret S.; Sovani, Manali (International Food Policy Research Institute, 2021)
We examine worker training by Chinese manufacturing firms using nationally representative firm-level data from both Ethiopia and Tanzania. While Chinese firms make up a relatively small portion of the manufacturing industry in both Ethiopia and Tanzania, at the firm-level they contribute significantly to both domestic employment and labor training. In both countries more than 85 percent of the workers employed by Chinese firms are local, and Chinese firms (and other foreign firms) are more likely to offer labor training than their domestic counterparts. However, we find evidence that Chinese firms underperform relative to other foreign firms in the share of local workers employed, and in Tanzania the difference is especially large for managerial positions.